Metal oxide catalyst for alcoholysis of PET (Polyethylene Terephthalate) as well as preparation method and application of metal oxide catalyst
By using a metal oxide catalyst composed of MgO, ZnO mixture and Fe, Cu, Mn and Bi metal oxides in the PET alcoholylation reaction, the problems of difficult catalyst separation, poor stability and low conversion are solved, and efficient PET conversion and high-purity BHET generation are achieved.
Patent Information
- Application Number
- CN202411748070.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing chemical recycling method of PET has problems such as difficulty in separating catalysts, poor stability and low conversion rates, making it difficult to achieve industrial production.
A metal oxide catalyst for alcoholylation of PET is used, which includes a mixture of MgO and ZnO as active components, and the metal oxides of Fe, Cu, Mn and Bi as additives, are synthesized by co-precipitation or rotary impregnation, and the metal oxide catalyst is calcined at 500 to 700°C.
The catalyst exhibits high efficiency catalytic activity in the PET alcoholylation reaction, with PET conversion rate reaching more than 90%, BHET yield reaching more than 80%, and the catalyst has high stability and can continuously catalyze the reaction.
Smart Images

Figure BDA0005164268310000041 
Figure BDA0005164268310000051 
Figure BDA0005164268310000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material degradation and recycling, and in particular to a metal oxide catalyst for alcoholysis of PET and a preparation method and application thereof. Background Art
[0002] Polyethylene terephthalate (PET) is made by transesterification of dimethyl terephthalate and ethylene glycol or esterification and polycondensation of terephthalic acid and ethylene glycol. The world's total PET production capacity is about 150 million tons. It is mainly used to produce fibers, plastic bottles and films. It is also an excellent engineering plastic material. However, due to the excellent chemical stability of PET, its products are difficult to degrade autonomously. Therefore, exploring PET recycling technology is conducive to the recycling of resources and helps environmental protection.
[0003] The recycling methods of PET are divided into physical recycling and chemical recycling. The physical recycling method is divided into mechanical recycling and energy recycling. Among them, mechanical recycling is to produce products for different purposes through a series of processes such as cutting, crushing, and melting. This method has low processing efficiency, and the side reactions caused by pyrolysis reduce the performance of the recycled products; energy recovery is to provide energy by directly incinerating waste plastics. The incineration process of this method will produce toxic gases such as black smoke and dioxins, which are harmful to human health. The above method has a simple process, and the performance of the plastic is reduced during the recycling process, and only low-quality plastics can be produced. The chemical recycling method aims to convert waste plastics into high-value-added chemicals. In contrast, the chemical recycling method is the best way to achieve closed-loop recycling of resources. It can process PET materials that are difficult to recycle and obtain high-quality recycled products, which is more in line with the development direction of sustainable recycling technology.
[0004] Currently, the main chemical recycling methods for PET are hydrolysis and alcoholysis. The hydrolysis method generally has problems such as high temperature and high pressure, corrosion of equipment, and environmental pollution. Among the alcoholysis methods, the methanol alcoholysis method has a high production cost, while the ethylene glycol alcoholysis method has a simple process, low energy consumption, produces a high value-added product, ethylene terephthalate (BHET), and is suitable for industrial production. However, this recycling method has challenges such as difficulty in catalyst separation, poor stability, and low conversion rate. For example, Chinese patent application CN114849714A discloses a method for preparing a solid base catalyst for alcoholysis of PET, wherein magnesium chloride, β-alanine and nickel chloride are dissolved in deionized water to obtain a mixed aqueous solution, which is filtered, dried and calcined to obtain a magnesium-nickel bimetallic oxide solid base catalyst, which is reacted at 180-190°C for 1-2h to obtain a maximum BHET yield of 91.15%. However, the solid base catalyst is used for the alcoholysis reaction of PET without considering and regulating the chemical stability of the catalyst, and it cannot be applied to industrial production. Chinese patent application CN118543369A discloses a class of zinc carboxylate catalysts, a preparation method and their application in the alcoholysis of PET, and a class of zinc carboxylate catalysts with a special "Y"-shaped structure are prepared for efficient catalysis of the ethylene glycol alcoholysis reaction of PET, with a catalytic efficiency of up to 104-105g PET / mole catalyst / hour, however, this method does not maintain an ideal BHET yield at a higher PET degradation rate, and the zinc carboxylate catalyst is dissolved in the liquid product as a homogeneous catalyst. The above disadvantages increase the separation cost; Chinese patent application CN115055175A discloses a preparation method of a defective zinc oxide nanosheet catalyst for alcoholysis of PET, in which a surfactant and an ethanolamine aqueous solution are successively added to zinc chloride, and then defective zinc oxide is obtained by filtering and roasting, showing a higher BHET yield, but the surfactant and ethanolamine solution added during the catalyst synthesis process make its production cost higher, making it difficult to maintain large-scale production.
[0005] In view of this, the present invention studies a simple and feasible catalyst synthesis method, which can efficiently catalyze the alcoholysis reaction of PET to obtain a higher BHET yield and a higher product purity, so as to facilitate the smooth progress of subsequent large-scale production. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a metal oxide catalyst for alcoholysis of PET and a preparation method and application thereof. The catalyst not only efficiently catalyzes the alcoholysis reaction of PET, but also simultaneously obtains a higher BHET yield and purity.
[0007] The technical solution adopted by the present invention is:
[0008] In a first aspect, the present invention provides a metal oxide catalyst for alcoholysis of PET, the catalyst comprising an active component and an auxiliary agent; the active component is a mixture of MgO and ZnO, the auxiliary agent is one of the metal oxides of Fe, Cu, Mn, and Bi, and the loading amount of the auxiliary agent is 0.1 to 5 wt% calculated based on the single substance of the metal element of the auxiliary agent component.
[0009] Furthermore, the auxiliary agent is one of the metal oxides of Fe and Bi.
[0010] Furthermore, the molar ratio of ZnO to MgO in the active component is 2 to 10:1.
[0011] Furthermore, the molar ratio of ZnO to MgO in the active component is 4 to 6:1.
[0012] Furthermore, in the catalyst, the loading amount of the auxiliary agent is 0.1 to 1 wt % calculated based on the single substance of the metal element of the auxiliary agent component.
[0013] In a second aspect, the present invention provides a method for preparing a metal oxide catalyst for alcoholysis of PET, comprising the steps of:
[0014] (1) preparing a metal salt aqueous solution of an active component, adding Na2CO3 to adjust the pH to 8-10, filtering, drying, and grinding the precipitate to obtain a Zn-Mg precursor powder;
[0015] (2) preparing a metal salt ethanol solution of an auxiliary component, adding the Zn-Mg precursor powder of step (1), stirring and heating to completely evaporate the ethanol solvent, and drying and grinding the evaporated solid matter to obtain a solid powder;
[0016] (3) The solid powder ground in step (2) is placed in a calcining furnace and heated to 500-700° C., and calcined in an air atmosphere for 1-5 hours to obtain a metal oxide catalyst powder.
[0017] Furthermore, the heating rate during calcination in step (3) is 2 to 5°C / min.
[0018] In a third aspect, the present invention also provides an application of a metal oxide catalyst for alcoholysis of PET in alcoholysis of waste PET.
[0019] Furthermore, the application method is: adding waste PET and metal oxide catalyst into a reaction kettle, adding ethylene glycol, heating to 180-200° C. and reacting for 2-4 hours to obtain a BHET product.
[0020] Furthermore, the added amount of the metal oxide catalyst is 5% to 20% of the mass of PET, and the mass ratio of PET to ethylene glycol is 1:10 to 40.
[0021] The beneficial effects of the present invention are:
[0022] The invention provides a metal oxide catalyst for alcoholysis of PET and a preparation method and application thereof. The metal oxide catalyst is used in the alcoholysis reaction of waste gas PET and ethylene glycol, can catalyze PET and ethylene glycol to generate BHET, has high catalytic activity, can make the PET conversion rate reach more than 90%, the PET conversion rate can reach up to 99.61%, the BHET yield can reach more than 80%, the BHET yield can reach up to 97.93%, and the catalyst has high stability during the reaction process, can continuously catalyze the alcoholysis reaction of PET and ethylene glycol. DETAILED DESCRIPTION
[0023] The present invention provides a metal oxide catalyst for alcoholysis of PET and a preparation method and application thereof. To make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0024] The invention provides a metal oxide catalyst for alcoholysis of PET, the catalyst comprising an active component and an auxiliary agent; the active component is a mixture of MgO and ZnO, the auxiliary agent is one of the metal oxides of Fe, Cu, Mn and Bi, and the auxiliary agent is preferably one of the metal oxides of Fe, Mn and Bi, and more preferably, the auxiliary agent is Fe or Bi.
[0025] Specifically, the molar ratio of ZnO to MgO in the above active components is 2 to 10:1, preferably, the molar ratio of ZnO to MgO is 4 to 6:1, and more preferably, the molar ratio of ZnO to MgO is 5:1.
[0026] Specifically, in the catalyst, the loading amount of the auxiliary agent is 0.1-5wt% calculated based on the metal element of the auxiliary agent component, preferably, the loading amount of the auxiliary agent is 0.1-1wt%, and more preferably, the loading amount of the auxiliary agent is 0.5wt%.
[0027] The metal oxide catalyst for alcoholysis of PET is synthesized by coprecipitation or rotary evaporation impregnation method, comprising the steps of:
[0028] (1) Preparing a metal salt of an active component into a precursor aqueous solution, adding Na2CO3 to adjust the pH to 8-10, filtering, drying, and grinding the precipitate to obtain a Zn-Mg precursor powder;
[0029] (2) preparing a metal salt ethanol solution of an auxiliary component, adding the Zn-Mg precursor powder of step (1), stirring and heating to completely evaporate the ethanol solvent, and drying and grinding the evaporated solid matter to obtain a solid powder;
[0030] (3) placing the solid powder ground in step (2) in a calcining furnace and heating the temperature to 500-700° C. at a heating rate of 2-5° C. / min, and calcining in an air atmosphere for 1-5 h to obtain a metal oxide catalyst powder.
[0031] Specifically, in a preferred embodiment of the present invention, the precursor aqueous solution of the active component Zn is zinc chloride or zinc nitrate, and the precursor aqueous solution of the active component Mg is magnesium chloride or magnesium nitrate.
[0032] The above-mentioned metal oxide catalyst is used for alcoholysis of waste PET, specifically, the metal oxide catalyst of the present invention is used for the alcoholysis process of PET ethylene glycol, that is, the waste PET and the metal oxide catalyst are added into a reactor, and then added into ethylene glycol, and the temperature is raised to 180-200° C. for reaction for 2-4 hours to obtain a BHET product, wherein the addition amount of the metal oxide catalyst is 5%-20% of the mass of the PET, preferably 10%-20%; the mass ratio of PET to ethylene glycol is 1:10-40, preferably 1:20-40, and more preferably 1:40.
[0033] The above PET glycol alcoholysis reaction process is as follows:
[0034]
[0035] The metal oxide catalyst has good catalytic performance in the waste PET alcoholysis process and can catalyze the alcoholysis of PET and ethylene glycol to generate BHET.
[0036] Example 1
[0037] This embodiment provides a metal oxide catalyst Fe / ZnO5-MgO1 for alcoholysis of PET, and the specific steps are as follows:
[0038] (1) 8.369 g ZnCl2 and 2.363 g MgCl2 solids were dissolved in 100 ml deionized water, stirred evenly and set aside, and then saturated Na2CO3 aqueous solution was slowly added dropwise while stirring, and a white precipitate gradually appeared during the process. The solution was added dropwise until the pH value was 9.0, and the addition was stopped. The stirring was continued for 30 min, and the stirring was stopped. The white solid was filtered to obtain a white solid. The solid matter after filtration was dried at 120°C for 12 h, and after drying, it was ground to obtain a Zn-Mg precursor powder;
[0039] (2) Dissolve 0.216 g of ferric nitrate nonahydrate in 50 ml of anhydrous ethanol, stir well and set aside, add Zn-Mg precursor powder during stirring, stir and heat at 70°C until all the solvent is completely evaporated, dry the evaporated solid material at 120°C for 12 h, grind it after drying, and then calcine it at 600°C in air atmosphere for 3 h at a heating rate of 3°C / min to finally obtain the catalyst powder Fe / ZnO5-MgO1.
[0040] Example 2
[0041] The difference between this embodiment and embodiment 1 is that the ratio of active components is different, and the other aspects are the same.
[0042] In this embodiment, the amount of zinc chloride and magnesium chloride added is adjusted to 6.698g, 4.725g and 9.127g, 1.288g, that is, the molar ratio of the active components MgO and ZnO is 2:1 and 10:1, and the obtained catalysts are Fe / ZnO2-MgO1 and Fe / ZnO2-MgO1, respectively. 10 -MgO1.
[0043] Example 3
[0044] The difference between this embodiment and embodiment 1 is that the auxiliary agent components are different, and the other components are the same.
[0045] In this embodiment, the auxiliary agents used are Cu, Mn, and Bi. Specifically, 0.088g, 0.098g, and 0.57g of copper nitrate, manganese nitrate, and bismuth chloride are weighed respectively and loaded on the Zn-Mg precursor powder obtained by precipitation method. The final catalysts obtained are Cu / ZnO5-MgO1, Mn / ZnO5-MgO1, and Bi / ZnO5-MgO1 respectively.
[0046] Example 4
[0047] The difference between this embodiment and embodiment 1 is that the loading amount of the auxiliary component Fe is different, and the other aspects are the same.
[0048] In this embodiment, the addition amount of ferric nitrate nonahydrate is adjusted to 0.043g, 0.432g, 2.16g, and 4.32g, that is, the loading amount of the auxiliary component Fe is 0.1%, 1%, 5%, and 10%, respectively, and the obtained catalysts are Fe(0.1) / ZnO5-MgO1, Fe(1) / ZnO5-MgO1, Fe(5) / ZnO5-MgO1, and Fe(10) / ZnO5-MgO1, respectively.
[0049] Example 5
[0050] The difference between this embodiment and embodiment 3 is that the loading amounts of the auxiliary components Cu, Mn and Bi are different, and the others are the same.
[0051] In this embodiment, the amount of copper nitrate added is adjusted to 0.018g and 0.18g, the amount of manganese nitrate added is adjusted to 0.02g and 0.2g, and the amount of bismuth chloride added is adjusted to 0.012g and 0.12g, that is, the loading amounts of the auxiliary components Cu, Mn and Bi are 0.1% and 1%, respectively. The obtained catalysts are Cu(0.1) / ZnO5-MgO1, Cu(1) / ZnO5-MgO1, Mn(0.1) / ZnO5-MgO1, Mn(1) / ZnO5-MgO1, Bi(0.1) / ZnO5-MgO1, and Bi(1) / ZnO5-MgO1, respectively.
[0052] Application Example 1
[0053] The Fe / ZnO2-MgO1, Fe / ZnO5-MgO1, Fe / ZnO prepared in Example 1 and Example 2 were 10 -MgO1 catalyst is used in PET and ethylene glycol alcoholysis reactions respectively. The specific application steps are as follows:
[0054] Weigh 0.5g of metal oxide catalyst and 5g of PET into an intermittent stirring reactor, add 60ml of ethylene glycol, set the reaction temperature to 200℃, stir at 800rpm, and continue the reaction for 3h. BHET is generated in the reaction process. After stopping the reaction, add 60ml of 80℃ hot water and stir at 500rpm for 1h to fully dissolve the BHET monomer. Then perform chromatographic analysis, cool the filtrate to 5℃, filter the precipitated BHET monomer, and dry at 80℃ for 10h to obtain BHET crystals. During chromatographic analysis, the obtained BHET crystals are compared with commercial BHET-C by infrared testing to detect their purity.
[0055] For the above Fe / ZnO2-MgO1, Fe / ZnO5-MgO1, Fe / ZnO 10 The BHET prepared by -MgO1 catalyst was subjected to relevant performance tests, and the test results are shown in Table 1 below.
[0056] Table 1 Test results of PET alcoholysis catalyzed by catalysts with different active component ratios
[0057]
[0058] According to the test results in Table 1, it can be seen that the ratio of the two active components, ZnO and MgO, has little effect on the catalyst stability, but has a great influence on the PET conversion rate and BHET yield. The Fe / ZnO-MgO catalyst has the highest PET conversion rate and BHET yield when the molar ratio of ZnO:MgO is 5.
[0059] Application Example 2
[0060] The difference between this application example and application example 1 is that in this application example, the Fe / ZnO5-MgO1 catalyst of example 1, the Cu / ZnO5-MgO1, Mn / ZnO5-MgO1, Bi / ZnO5-MgO1 catalysts of example 3 and the Cu(0.1) / ZnO5-MgO1, Cu(1) / ZnO5-MgO1, Mn(0.1) / ZnO5-MgO1, Mn(1) / ZnO5-MgO1, Bi(0.1) / ZnO5-MgO1, Bi(1) / ZnO5-MgO1 catalysts of example 5 are respectively applied to PET and ethylene glycol alcoholysis reactions, and the alcoholysis reaction processes are the same.
[0061] The BHET prepared by the above-mentioned Fe / ZnO5-MgO1, Cu / ZnO5-MgO1, Mn / ZnO5-MgO1 and Bi / ZnO5-MgO1 catalysts were respectively subjected to relevant performance tests, and the test results are shown in Table 2 below.
[0062] Table 2 Test results of PET alcoholysis catalyzed by different additive components and catalysts
[0063]
[0064] According to the test results in Table 2, it can be seen that the auxiliary component has a great influence on the PET conversion rate, BHET yield and catalyst stability. Among them, the catalyst with Fe as the auxiliary component loaded on ZnO-MgO has the best performance in catalyzing PET alcoholysis to BHET, not only with high PET conversion rate and BHET yield, but also with good catalyst stability; in addition, the catalyst with Bi as the auxiliary component loaded on ZnO-MgO also has a relatively high PET conversion rate and BHET yield, but its stability is poor; Cu and Mn can also catalyze the alcoholysis of PET and ethylene glycol to a certain extent, and their PET conversion rate can reach more than 80%, but their catalytic performance is relatively weak compared with Fe and Bi.
[0065] Application Example 3
[0066] The difference between this application example and application example 1 is that in this application example, the Fe(0.5) / ZnO5-MgO1 catalyst of example 1 and the Fe(0.1) / ZnO5-MgO1, Fe(1) / ZnO5-MgO1, Fe(5) / ZnO5-MgO1 and Fe(10) / ZnO5-MgO1 catalysts of example 4 are respectively applied to PET and ethylene glycol alcoholysis reactions, and the alcoholysis reaction processes are the same.
[0067] The BHET prepared by the Fe(0.5) / ZnO5-MgO1 of the above-mentioned Example 1, the Fe(0.1) / ZnO5-MgO1, Fe(1) / ZnO5-MgO1, Fe(5) / ZnO5-MgO1, and Fe(10) / ZnO5-MgO1 catalysts of Example 4 were respectively subjected to relevant performance tests, and the test results are shown in Table 3 below.
[0068] Table 3 Performance results of PET alcoholysis catalyzed by catalysts with different additive component loadings
[0069]
[0070] According to the test results in Table 3, it can be seen that the loading amount of the auxiliary component has a great influence on the PET conversion rate, the BHET yield and the catalyst stability. When the loading amount of the auxiliary component Fe is 0.1-1wt%, the PET conversion rate and the BHET yield are relatively high, but when the loading amount of the auxiliary component Fe is 0.1wt%, the stability of the catalyst is poor; when the loading amount of the auxiliary component Fe is 0.5wt%, the catalytic performance is optimal, with high PET conversion rate, high BHET yield and good stability.
[0071] Application Example 4
[0072] The difference between this application example and application example 1 is that this application example uses the Fe / ZnO5-MgO1 catalyst prepared in Example 1 to react at different reaction temperatures, different reaction times, different catalyst addition amounts, and different ethylene glycol addition amounts. The specific reaction conditions and the test results of the BHET products prepared under different reaction conditions are shown in Table 4 below.
[0073] Table 4 Catalytic PET alcoholysis performance results under different reaction conditions
[0074]
[0075] According to the test results in Table 4, it can be seen that the reaction temperature, reaction time, catalyst to PET mass ratio, ethylene glycol to PET mass ratio have a great influence on the alcoholysis reaction. When the reaction temperature is 180-200°C, the reaction time is 3h, the mass of the catalyst is 10-20% of the mass of PET, and the mass of ethylene glycol is 20-40 times the mass of PET, the PET conversion rate and BHET yield of the alcoholysis reaction are relatively high. Especially when the reaction temperature is 200°C, the reaction time is 3h, the mass of the catalyst is 10% of the mass of PET, and the mass of ethylene glycol is 40 times the mass of PET, the PET conversion rate and BHET yield of the alcoholysis reaction are the highest.
[0076] It should be noted that some parts not described in the present invention can be implemented by adopting or drawing on existing technologies.
[0077] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A metal oxide catalyst for alcoholysis of PET, characterized in that: The catalyst comprises an active component and an auxiliary agent; the active component is a mixture of MgO and ZnO, the auxiliary agent is one of metal oxides of Fe, Cu, Mn and Bi, and the loading amount of the auxiliary agent is 0.1-5wt% calculated based on the single substance of the metal element of the auxiliary agent component.
2. The metal oxide catalyst for alcoholysis of PET according to claim 1, characterized in that: The auxiliary agent is one of metal oxides of Fe and Bi.
3. The metal oxide catalyst for alcoholysis of PET according to claim 1, characterized in that: The molar ratio of ZnO to MgO in the active component is 2 to 10:
1.
4. The metal oxide catalyst for alcoholysis of PET according to claim 3, characterized in that: The molar ratio of ZnO to MgO in the active component is 4-6:
1.
5. The metal oxide catalyst for alcoholysis of PET according to claim 1, characterized in that: In the catalyst, the loading amount of the auxiliary agent is 0.1-1 wt % calculated based on the simple substance of the metal element of the auxiliary agent component.
6. The method for preparing a metal oxide catalyst for alcoholysis of PET according to any one of claims 1 to 5, characterized in that: Includes steps: (1) preparing a metal salt aqueous solution of an active component, adding Na2CO3 to adjust the pH to 8-10, filtering, drying, and grinding the precipitate to obtain a Zn-Mg precursor powder; (2) preparing a metal salt ethanol solution of an auxiliary component, adding the Zn-Mg precursor powder of step (1), stirring and heating to completely evaporate the ethanol solvent, and drying and grinding the evaporated solid matter to obtain a solid powder; (3) The solid powder ground in step (2) is placed in a calcining furnace and heated to 500-700° C., and calcined in an air atmosphere for 1-5 hours to obtain a metal oxide catalyst powder.
7. The method for preparing a metal oxide catalyst for alcoholysis of PET according to claim 6, characterized in that: The heating rate during calcination in step (3) is 2 to 5°C / min.
8. Use of the metal oxide catalyst for alcoholysis of PET as claimed in any one of claims 1 to 5 in alcoholysis of waste PET.
9. The use according to claim 8, characterized in that: The application method is as follows: waste PET and metal oxide catalyst are added into a reaction kettle, and ethylene glycol is added, and the temperature is raised to 180-200° C. to react for 2-4 hours to obtain a BHET product.
10. The use according to claim 9, characterized in that: The added amount of the metal oxide catalyst is 5% to 20% of the mass of PET, and the mass ratio of PET to ethylene glycol is 1:10 to 40.
Citation Information
Patent Citations
Preparation method of solid base catalyst for alcoholysis of PET
CN114849714A
Preparation method of defect-state zinc oxide nanosheet catalyst for alcoholysis of PET
CN115055175A
Zinc carboxylate catalyst, preparation method and application of zinc carboxylate catalyst in alcoholysis of polyethylene terephthalate
CN118543369A
Ester exchange catalyst for glycol to degrade polyethylene glycol terephthalate and preparation method thereof
CN101698150A
Method for removing phenylacetylene in presence of styrene
CN102408299A
Cited By
Preparation method of metal-iron-niobium catalyst and application of alcoholysis waste plastics
CN122399826A